El eslabón perdido de Luisa Carnés: Une famille déchirée par l’exil - Carole Viñals (Les Cahiers ALHIM)
This article studies the effects of the migration on a family throuth a novel, El eslabón perdido, based on Luisa Carnes’s personal experience of exil in Mexico after the defeat of the Spanish republic in 1939. While from 1951, any hope of return seems lost, the central figure did not succeed in adapting himself. It goes quite otherwise for the two children who arrived in Mexico when the were young kids. The exile breaks the family, the father appearing as the lacking link. Nevertheless the ambigüity of the family relationships after the exile, Ramon, the son of Luisa Carnes, seems to have shown his loyalty to family values, proving maybe this way that the exile is a test for the family links but does not necessarily succeed in breaking them.